Intracranial tumors mimicking benign paroxysmal positional vertigo: A case series - Chen, Yuan Xing; Sun, Han Jun; Mu, Xue Tao; Jiang, Chao; Wang, Hui Bing; Zhang, Qing Hua; Qu, Yuan Yi; Li, Jian; Zhou, Ling Ling; Zhao, Long Zhu; Yu, Ning; Sun, Qing (Frontiers in Neurology, 2022)
Background: A few intracranial lesions may present only with positional vertigo which are very easy to be misdiagnosed as benign paroxysmal positional vertigo(BPPV), the clinicians should pay more attention to this diseases. Objectives: To analyze the clinical characteristics of 6 patients with intracranial tumors who only presented with positional vertigo to avoid misdiagnosing the diseases. Material and Methods: Six patients with intracranial tumors who only presented with positional vertigo treated in our clinic between May 2015 to May 2019 were reviewed, and the clinical symptoms, features of nystagmus, imaging presentation, and final diagnosis of the patients were evaluated. Results: All patients presented with positional vertigo and positional nystagmus induced by the changes in head position or posture, including 1 case with downbeating nystagmus in positional test, 2 cases with leftbeating nystagmus, 1 case with apogeotropic nystagmus in roll test, 1 cases with rightbeating nystagmus, 1 case with left beating and upbeating nystagmus. Brain MRI: showed the regions of the tumors were in the vermis of the cerebellum, the fourth ventricle, the lateral ventricle, and the cerebellar hemisphere. Conclusions and Significance: When present of nystagmus features that are not consistent with BPPV, patients should receive an brain MRI examination to distinguish BPPV from intracranial diseases.